Efficacy of Articaine or Eugenol for Pain Relief after Emergency Coronal Pulpotomy in Teeth with Irreversible Pulpitis: A Randomized Clinical Trial - Fernandez De Grado Gabriel; Bourdin Clément; Fioretti Florence; Musset Anne-Marie; Offner Damien (MDPI AG, 2023)
Irreversible pulpitis is an extremely painful dental pathology. Its emergency treatment, pulpotomy, should include the use of a pulp dressing in the pulp chamber until the final treatment. Various antalgic products have been suggested as efficient medications to relieve the patient's pain and are commonly used, but data for scientific validation are scarce. Objective: We evaluated the efficacy of articaine or eugenol in the diminution of pain after pulpotomy. Design: We included 100 patients with irreversible pulpitis and evaluated their initial pain levels. Pain was measured using a 0-10 numeric rating scale. After treatment through pulpotomy, we randomized them into two groups using either articaine or eugenol as a pulp dressing and evaluated their pain level at 1, 3 and 7 days. Results: Initial pain levels were severe (7.53). The use of painkillers was not associated with lower levels of pain. Both treatments showed great efficiency on day 1, with stronger efficiency of eugenol than articaine, showing a decrease of 6.24 versus 4.89 (p = 0.025). Both treatments were efficient, whatever the age or sex of the patient, the initial pain level, and the causal tooth. Conclusion: Pulpotomy is an efficient way to relieve pain, using either articaine or eugenol. When choosing a pulp dressing, eugenol should be the first choice.